2022
DOI: 10.1155/2022/4492132
|View full text |Cite
|
Sign up to set email alerts
|

Antiobesity and Hepatoprotective Effects of Protein Hydrolysates Derived from Protaetia brevitarsis in an Obese Mouse Model

Abstract: Background. Obesity induced by excessive nutrients can cause fatty liver and metabolic dysfunction, which leads to hepatic dysfunction and local/systemic inflammatory responses. Previously, we analyzed the antioxidant, antilipotoxicity, and anti-inflammatory effects of protein hydrolysates in vitro. The aim of the present study is to investigate the antiobesity and hepatoprotective effects of protein hydrolysates derived from Protaectia brevitas (PHPB) in an obese mouse model. Methods. For this in vivo study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Therefore, alcohol consumption leads to fatty liver, which can create an environment in the liver that is more susceptible to alcoholic liver damage. It has been reported that the protein hydrolysates of P. brevitarsis larvae improved liver injury by regulating mRNA expressions of AP2/FABP4, AMPKα2, and PPAR-γ and decreasing adipocyte size in high-fat diet (HFD)-induced fatty liver mice [ 67 ]. Ahn et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, alcohol consumption leads to fatty liver, which can create an environment in the liver that is more susceptible to alcoholic liver damage. It has been reported that the protein hydrolysates of P. brevitarsis larvae improved liver injury by regulating mRNA expressions of AP2/FABP4, AMPKα2, and PPAR-γ and decreasing adipocyte size in high-fat diet (HFD)-induced fatty liver mice [ 67 ]. Ahn et al .…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro studies reported that P. brevitarsis larvae exhibited anti-inflammatory activity in LPS-induced RAW264.7 cells [ 73 , 74 ]. In addition, P. brevitarsis larvae reduced inflammatory cell infiltration in the adipose tissue of HFD-induced mice [ 67 ]. In a previous study, arginine improved inflammatory changes in the liver by decreasing levels of endotoxin, MDA, and the expression of p-NF-κB, and TNF-α in ethanol-induced rats [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Lee et al . (2022) observed that the levels of serum TCHO and LDLC are significantly reduced and the serum HDLC level is increased in the protein hydrolysates derived from PBS extract‐treated group. There is no clear explanation for this discrepancy; however, it may be partially explained by the absence of a proportional pattern of TCHO, HDLC, and LDLC levels following the administration of the PBS extract.…”
Section: Resultsmentioning
confidence: 99%
“…These outcomes are inconsistent with those of Ahn et al (2019), who found a reduction in serum lipid parameters after the administration of PBS extract to HFD-fed obese mice. Moreover, Lee et al (2022) observed that the levels of serum TCHO and LDLC are significantly reduced and the serum HDLC level is increased in the protein hydrolysates derived from PBS extract-treated group. There is no clear explanation for this discrepancy; however, it may be partially explained by the absence of a proportional pattern of TCHO, HDLC, and LDLC levels following the administration of the Note: The mean differences between the control and each experimental group were measured using an independent sample t-test.…”
Section: Serum Cholesterol Metabolitesmentioning
confidence: 90%
“…Currently, the edible insects reported to inhibit and treat obesity and metabolic diseases mainly include Tenebrio molitor, Acheta domesticus, Locusta migratoria, Allomyrina dichotoma, etc [16][17][18]. As for P. brevitarsis, P. brevitarsis protein hydrolysate could effectively reduce the levels of blood urea nitrogen, total cholesterol and triglyceride, and increase the high-density lipoprotein, IL-6, TNF-α and IGF-1 in serum of the HFD-fed mice [19]. Meanwhile, P. brevitarsis 70% ethanol extract could effectively reduce the body weight, liver lipid accumulation and serum parameters of obese mice, and inhibit the expression of C/EBPa, FAS and aP2 genes in 3T3-L1 adipocytes [20].…”
Section: Introductionmentioning
confidence: 99%